Emerging applications of read profiles towards the functional annotation of the genome - Pundhir, Sachin; Poirazi, Panayiota; Gorodkin, Jan (Frontiers in Genetics, 2015)
Functional annotation of the genome in various species is important to understand their phenotypic complexity. The road towards functional annotation involves several challenges ranging from experiments on individual molecules to large-scale analysis of high-throughput sequencing (HTS) data. HTS data is typically a result of the protocol designed to address specific research questions. The sequencing results in reads, which when mapped to a reference genome often leads to the formation of distinct patterns (read profiles). Interpretation of these read profiles are essential for the analysis in relation to the research question addressed. Several strategies have been employed at varying levels of abstraction ranging from a somewhat ad hoc to a more systematic analysis of read profiles. These include methods which can compare read profiles, e.g. from direct (non-sequence based) alignments to classification of patterns into functional groups. In this review, we highlight the emerging applications of read profiles for the annotation of non-coding RNA and cis-regulatory regions such as enhancers and promoters. We also discuss the biological rationale behind their formation.